The Technology of Geodesic Dome Design on Cinematography and Interactive Tourist Information Centre Building in Penang - Yusof, Hanita (International Journal of Sustainable Construction Engineering and Technology, 2021)
Penang is among one of the states in Malaysia that embrace their cultural heritage and maintain their architectural style from early decade. Its population is extremely diverse in ethnicity, having rich culture, linguistic and religion. The issue of sustainability arose when we have the intention to ‘sustain’ a culture for tourism purpose but at the same time it contradicted with the process of urbanization and having rapid development of architectural style and recent technology. This research studied on the proposal of upgrading it into a more advance technology yet still maintaining the earlier era of architectural style. In order to keep this heritage sustain, design approaches may have a combination of two era which is colonial era style with modernism style. Penang virtual and interactive tourist information centre are design to accommodate tourist with an information transferred platform using high technology which is providing a 5D Cinematography and 9D technology. Having a geodesic dome for Penang Virtual and Interactive Tourist Information Centre in the design is a great solution because to build a 5D cinematography can be functional by using a geodesic dome. It also shows that 5D cinematography can be functioning without having columns. Geodesic dome is one of the building element that can replace column to build a high technology of cinema room. The issue on having large spaces and high ceiling for cinema has been solved. 5D cinematography using an 180ᵒ curve screen obviously needs a strong structure which are curve to hold the screen and it is solved by designing the geodesic dome. The issue on sustaining their cultural heritage is also achieved by combining the geodesic dome design with colonial era of architectural style on the building façade.